Application of Game-Assisted Problem-Based Learning to Improve Critical Thinking Skills and Learning Motivation of Students - Siti Mariyatul Qibtiyah; Umi Solikah; Ahmad Fauzi; Abdulkadir Rahardjanto (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
The majority of student learning processes in schools have not encouraged students to improve critical thinking process skills. In fact, it is important for students to have these skills to deal with complex problems in the future, so that learning strategies are needed to improve these skills. This classroom action research aims to improve students' critical thinking skills and learning motivation in game-assisted PBL learning. This research consisted of two cycles consisting of the planning, implementation, and reflection stages. The research subjects were 27 students of class X-11 State Senior High School 1 Batu. The data were obtained from the results of the pre-test and post-test for each learning cycle. The treatment in this study was the PBL learning model with the help of games. The dependent variable used was critical thinking skills and student learning motivation as measured using the critical thinking indicator guide according to Anderson. The results of this study indicate an increase in students' critical thinking skills and learning motivation obtained from the analysis of test results and observations. This shows that PBL is effectively implemented and can equip students with certain skills.